A contaminação hídrica e os fatores críticos de sucesso na gestão em serviços de transplante de medula óssea (TMO) - Stangueti, Ernesto (2014)
Government agencies, in Brazil and in developed countries, have established guidelines for water safety in the community, in particular in the health care of immunocompromised pacients, in this case environments hospitals that receive such patients should provide higher standards for water quality by taking immediate action to prevent waterborne infections. This paper aims to assess how hospitals that perform bone marrow transplantation (BMT) manage the critical success factors in the prevention of water contamination of their patients and extract from these assessments a model of management of hospital logistics in relation to administrative processes needed for effective control of such infection. To this end, it was chosen a case study. The interviews were conducted with professional members of Commissions Infection Control in four hospitals located in São Paulo who perform BMT. The data were analyzed using the methodology of the Collective Subject Discourse (CSD) described by Lefèvre & Lefèvre (2003). The main management practices related to water contamination were: cleaning and disinfection of water tanks and bacteriological control, installation of filters for high power filtering at the point of use (taps and showers), supply of mineral water industrialized for consumption of patients of BMT unit, institution management committee comprising representatives from all areas involved in the operations of the BMT unit. Thus, this work contributes to technological and social practice through the development of a model of hospital logistics management, collaborating in preventing Related Infections at Health Care (IRAS) in units of BMT.